2015
DOI: 10.1002/adem.201400573
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and Properties of Aluminum–Copper Lap‐Welded Joints by Cold Metal Transfer Technology

Abstract: In this paper, 1 mm thick 1060 aluminum sheet and pure copper were joined using AlCu5 filler wire by cold metal transfer (CMT). It was found that it is feasible to join aluminum to copper by this method, and a good wettability and weld appearance was usually obtained. The effect of heat input on the microstructure and tensile shear strength of joints was investigated. The results indicated that a continuous layer of intermetallic compounds (IMCs), i.e., Al4Cu9 (g), Al2Cu3 (e), and Al2Cu (u) was produced in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The results of a chemical composition analysis of the fracture surfaces are listed in Table 5, and the identified The BSE images of the Al/Cu dissimilar joint interface produced with the ad 2.3 at.% Ni are presented in Figure 5, and the results of chemical composition an IMC phases found in Figure 5c are shown in Table 4. Similar to the joint interf duced without alloying elements, the dissimilar interface had a typical reaction la responding to the joining between liquid Al and solid Cu [4,5,[12][13][14][15][16][17][18], i.e., a eutec ture formed in the Al fusion zone and an IMC layer adjacent to the Cu. The IM mainly comprised a thick Al2Cu layer, as shown in Figure 5b and Table 4, as wa in the joint produced without alloying elements (Figure 4).…”
Section: Fracture Location Within the Dissimilar Jointmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a chemical composition analysis of the fracture surfaces are listed in Table 5, and the identified The BSE images of the Al/Cu dissimilar joint interface produced with the ad 2.3 at.% Ni are presented in Figure 5, and the results of chemical composition an IMC phases found in Figure 5c are shown in Table 4. Similar to the joint interf duced without alloying elements, the dissimilar interface had a typical reaction la responding to the joining between liquid Al and solid Cu [4,5,[12][13][14][15][16][17][18], i.e., a eutec ture formed in the Al fusion zone and an IMC layer adjacent to the Cu. The IM mainly comprised a thick Al2Cu layer, as shown in Figure 5b and Table 4, as wa in the joint produced without alloying elements (Figure 4).…”
Section: Fracture Location Within the Dissimilar Jointmentioning
confidence: 99%
“…Therefore, many attempts using low heat-input welding have been made to reduce the thickness of the IMC layer. For instance, the application of brazing between liquid Al and solid Cu, such as arc brazing [12][13][14][15] and laser brazing [16][17][18], and solid-state joining, such as friction welding [19,20], friction stir welding [10,[21][22][23][24], and ultrasonic spot welding [25][26][27], successfully suppressed the growth of the IMC layer, thereby improving the mechanical properties of the dissimilar joints.…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al [10] obtained sound Al-Cu joints using cold metal transfer technology and it was shown that the strength of the joints reached a higher level due to the effect of the size of Al-Cu IMCs. Feng et al [11] joined aluminum to copper by CMT technology, the effect of heat input on the microstructure and tensile shear strength of joints was studied, and the results presented that different heat imputed resulted in the significant change of IMCs. Zhou et al [12] adapted a low heat input pulsed double-electrode gas metal arc welding (DE-GMAW) brazing method [13] to achieve Al-Cu reliable connection, the intermetallic compound was controlled by heat input, and the sound joint was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In this investigation, weld bead geometries such as depth of penetration (DOP), weld bead width, reinforcement height, dilution and contact angle have been studied. Feng et al [17] reported the dissimilar welding (pure copper + AA1060) using CMT process and concluded that the process is a feasible method to join dissimilar metals.…”
Section: Introductionmentioning
confidence: 99%